2016
DOI: 10.1016/j.tranon.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cancer Fluorescence Imaging Using A γ-Glutamyltranspeptidase-Specific Probe For Primary Lung Cancer

Abstract: BACKGROUND: We set out to examine the activity of γ-glutamyltranspeptidase (GGT) in lung cancer and the validity of γ-glutamyl hydroxymethyl rhodamine green (gGlu-HMRG) for intraoperative imaging of primary lung cancer. METHODS: GGT activities and mRNA expression levels of GGT1 (one of the GGT subtypes) in five human lung cancer cell lines were examined by fluorescence imaging and quantitative reverse transcription polymerase chain reaction. In vivo imaging of an orthotopic A549 xenograft model in nude mice wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…As GGT is overexpressed on the membranes of various cancer cells, gGlu-HMRG has been reported as a tool to detect breast cancer [ 12 ], lung cancer [ 9 ], colorectal tumors [ 10 ], head and neck squamous cell carcinoma [ 7 ], and prostate cancer [ 13 ]. The sensitivity and specificity of gGlu-HMRG in lung cancer detection are 43.8 and 84.9%, respectively [ 9 ]. gGlu-HMRG also reportedly enabled rapid fluorescence imaging of 54 and 76% of colorectal adenomas and carcinomas, respectively [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As GGT is overexpressed on the membranes of various cancer cells, gGlu-HMRG has been reported as a tool to detect breast cancer [ 12 ], lung cancer [ 9 ], colorectal tumors [ 10 ], head and neck squamous cell carcinoma [ 7 ], and prostate cancer [ 13 ]. The sensitivity and specificity of gGlu-HMRG in lung cancer detection are 43.8 and 84.9%, respectively [ 9 ]. gGlu-HMRG also reportedly enabled rapid fluorescence imaging of 54 and 76% of colorectal adenomas and carcinomas, respectively [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small tumors are reportedly rapidly detectable by fluorescence imaging in vivo [ 23 28 ]. Several studies have reported that GGT is highly expressed in cancer cell membranes, as determined by immunohistochemical methods [ 7 , 9 ]. In this study, 14 thyroid cancer samples among 16 cases were positive for GGT in the cell membranes; in contrast, cases involving non-cancerous or inflammatory lesions were negative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study it was observed that GGT1 was significantly expressed in breast cancer when compared with the control. The expression of tumor tissue GGT1 has also been shown in various cancers such as prostate (Kawakami et al 2017), epithelial (Lukic et al 2016), lung (Hino et al 2016), colorectal (Palaniappan et al 2016), overian (Mahata 2006), liver (Pavesi et al 1989), and breast (Banneau et al 2010).…”
Section: Discussionmentioning
confidence: 97%